Lithological Interpretation of Landslide Zone of Arjuna Road Kalongan Village East Ungaran Use Geomagnetic Method - Bustari, Ahdian Azri; Andi, Andi; Wibowo, Nugroho Budi; Niyartama, Thaqibul Fikri (POSITRON, 2024)
Arjuna Road in Kalongan Village, East Ungaran, which connects Semarang Regency with Demak Regency, has been cut off due to a landslide. Lithology as an internal controlling factor of landslide occurrence is important to be investigated. Research on the disaster has been conducted to determine the magnetic field anomaly and to interpret subsurface lithology using the geomagnetic method. The research was conducted on the landslide zone at Arjuna Road and its surrounding area using the geomagnetic method with looping data acquisition. The research area includes residential areas and plantation areas of residents with a research area of 1.3 Ã— 0.8 km2 with a total of 104 measurement points. Through the results and analysis of the research, it can be determined that the magnetic field anomalies in the research area range from 17.1 - 882.2 nT where the landslide zone dominantly has a high anomaly indicating the closer the area is to bedrock, and for residential areas and local plantations, the magnetic field anomalies vary from low to high depending on the topography and sediment thickness in the area. In addition, the subsurface lithology in the study area consists of clay soil, claystone, tuff, and volcanic breccia. The impermeable nature of the tuff and the water-low permeable clay soil causes the boundary between the clay soil and tuff layers to become slippery when water seepage occurs, resulting the landslides.